The Routledge Companion to World Literature and World History
1 online resource
Keywords: "The Routledge Companion to World Literature and World History is a comprehensive and engaging volume, combining essays from historians and literary academics to create a space for productive cross-cultural encounters between the two fields. In addition to the 27 essays, the Companion includes general introductions from two of the leading scholars of history and literature, David Damrosch and Patrick Manning, as well as personal testimonies from artists working in the area, and editorials asking provocative questions.The volume includes sections on:People with essays looking at World Literature, Intellectual Commerce, Religion, language and war, and Indigenous ethnographyNetworks and methods examining maps, geography, morality and the crises of world literatureTransformations including essays on race, colonialism, and the non-humanInterdisciplinary and groundbreaking, this volume brings to light various ways in which scholars of literature and history analyse, assimilate or reveal the intellectual heritage of the past, at the same moment as they try consciously to deal with an unending amount of new information and an awareness of global connections and discrepancies. Including work from leading academics in the field, as well as newer voices, the Companion is ideal for students and scholars alike."--Provided by publisher.